2021
DOI: 10.1097/ccm.0000000000005095
|View full text |Cite
|
Sign up to set email alerts
|

Transitions of Care After Critical Illness—Challenges to Recovery and Adaptive Problem Solving*

Abstract: Objective-Investigate the challenges experienced by survivors of critical illness and their caregivers across the transitions of care from intensive care to community, and the potential problem-solving strategies used to navigate these challenges.Design-Qualitative design -data generation via interviews and data analysis via the Framework Analysis method.Setting-Patients and caregivers from three continents, identified through the Society of Critical Care Medicine's THRIVE international collaborative sites (fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 32 publications
0
36
0
2
Order By: Relevance
“…across the recovery trajectory, beginning at the ICU event through months after hospital discharge (9,10). These and other qualitative studies have strongly suggested that spiritual and social supports are key facilitators for critical illness recovery (11)(12)(13).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…across the recovery trajectory, beginning at the ICU event through months after hospital discharge (9,10). These and other qualitative studies have strongly suggested that spiritual and social supports are key facilitators for critical illness recovery (11)(12)(13).…”
mentioning
confidence: 90%
“…Survivors of critical illness often report substantial physical, cognitive, and psychologic symptom burdens, which affects their quality of life, capacity to regain functional independence, and employment status for months to years after hospital discharge (1–8). In qualitative studies, critical illness survivors also describe ongoing spiritual and social support needs across the recovery trajectory, beginning at the ICU event through months after hospital discharge (9, 10). These and other qualitative studies have strongly suggested that spiritual and social supports are key facilitators for critical illness recovery (11–13).…”
mentioning
confidence: 99%
“…As the COVID-19 pandemic has unfolded, the controversial questions of tracheostomy timing, techniques, and early outcomes [1] , [2] , [3] , [4] , [5] , [6] have sometimes eclipsed the softer voices of patients, caregivers, and front-line workers. Yet, these perspectives are critical, as they can surface underappreciated or neglected needs across the continuum of care [7] , [8] , [9] , [10] and survivorship [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite critical care being an interdisciplinary and multi-professional subject in the acute phase, critical care personnel (i.e., physicians and nurses) are usually cut off from subsequent healthcare. While ICU follow-up clinics do exist in some care models (e.g., United Kingdom), the majority of critical care survivors do not have access to ICU follow-up clinics [12][13][14]. PICS awareness in outpatient care has probably increased due to the coronavirus disease 2019 (COVID-19) pandemic and long-haul COVID-19.…”
mentioning
confidence: 99%